Patient Perceptions on The Role of Nurses in Discharge Planning for Post-Neurosurgery Patients: A Qualitative Study - Liani Br Ginting; Ali Napiah Nasution; Elis Anggeria (Talenta Publisher, 2025)
Nurses play a vital role and bear primary responsibility in discharge planning due to their constant interaction with patients and families. Research on discharge planning in Indonesia, particularly for post-neurosurgery patients, is still limited and rarely explored in depth, especially using a qualitative approach. Through a qualitative approach, this study was able to reveal the perceptions, challenges, and strategies of nurses that are often not seen in quantitative data. This study aims to analyse the role of nurses in discharge planning for families of patients who have undergone neurosurgery. This study employed a descriptive qualitative approach using phenomenological methods. The number of participants or informants based on saturation data or redundancy concepts can generally be achieved using purposive techniques. In-depth interviews were used in data collection. The data analysis process in this study used Colaizzi's approach. This study produced nine themes based on the Modified Concept of Meleis' Transitional Nursing Theory and Roy's Adaptive Nursing Model Theory. including medical education, clarity of information, involving the family, addressing concerns, support for access to follow-up services, follow-up support, patient/family readiness, post-discharge challenges, recommendations for services. The impact of discharge planning carried out by nurses prior to discharge home results in patients and their families being prepared to carry out nursing actions at home. Nurses should always be mindful of their role in the discharge planning process because quality discharge planning is not merely an “administrative procedure before discharge,” but rather a strategic investment. Keyword: Patient Discharge Planning, Neurosurgery Procedure, Nursing Role